KESADARAN FONOLOGI PADA ANAK USIA PRASEKOLAH - K A Rahman; Fortuna Mazka; Elmanora Elmanora (Jurnal Ilmiah Universitas Batanghari Jambi, 2018)
Phonological awareness is one of a critical aspect in early literacy development that develop during preschool period. Phonological awareness is sensitivity to the sound structure of language. This study was conducted to analyse the phonological awareness in preschool children. This study was also identify learning activity in the class that support phonological awareness of preschool children. Research with cross sectional design was conducted in August-November 2016 in one kindergarten in Jambi City, Jambi Province, Indonesia. Data were collected through observation, child’s performance, and interview with teacher. The collected data were analyzed by descriptive analysis. Result showed that phonological awareness had arisen at the word, syllable, and onset-rime levels. However, children have difficulty in sounding syllables and rime. Teachers have supported the phonological awareness of children through playing and learning activities. However, the activities that has been given to children didn’t vary so not all of phonological awareness aspects got sufficient support.   Keywords: child learning, early childhood education, phonological awareness